Gharar dalam Praktik Kartel Non Harga: Perspektif Hukum Ekonomi Islam - Ramadhani, Alya; Rahmadi, Afdal; Meilani, Meilani (Fakultas Syariah IAIN Kendari, 2025)
This article discusses non-price cartel practices in the context of Islamic economic law, which often receive less attention than price cartels. Non-price cartels include quota setting, market distribution, and other collusion that harms consumers and creates injustice. From the perspective of Islamic economic law, which is based on the principles of justice, transparency, and the prohibition against gharar (uncertainty), this practice is clearly contrary to the ethical values adhered to. The research used is normative legal research with a qualitative approach. This approach was chosen because Islamic law emphasizes moral and ethical principles which cannot always be measured with quantitative data. This research focuses on analyzing the legal norms governing non-price cartel practices and how these practices conflict with the principles of justice, transparency and the prohibition against gharar in Islamic law. It was found that non-price cartels not only threaten market integrity, but can also generate dissatisfaction among consumers. This article suggests the need for stricter law enforcement and education for business actors to create awareness regarding the principles of Islamic economic law in preventing detrimental cartel practices. Keywords : Gharar, Islamic law, non-price cartel